PENGARUH VARIASI MENGAJAR GURU TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS X DI SMA NEGERI 1 BONE KECAMATAN BONE KABUPATEN BONE BOLANGO - Yeliyanti Pasune; Sudirman Sudirman; Maya Novrita Dama; Abdulrahim Maruwae; Rierind Koniyo (Consilium: Education and Counseling Journal, 2026)
The study aims to determine the magnitude of the influence of teacher teaching variations on student learning motivation in the Economics subject for Grade X at SMA Negeri 1 Bone, Bone Subdistrict, Bone Bolango Regency. This study employed a quantitative approach with simple linear regression. The study population consisted of 126 students. The data collection technique used in this study was the distribution of questionnaires to 33 respondents, while the data analysis techniques included normality tests, simple linear regression tests, t-tests (analysis of variance), and coefficient of determination tests. The results of this study show that there is a positive influence of teacher teaching variations on student learning motivation, in which 66.5% of the variability in the Student Learning Motivation variable in Economics subject for Grade X at SMA Negeri 1 Bone, Bone Subdistrict, Bone Bolango Regency, can be explained by the Teacher Teaching Variations variable, while the remaining 33.5% is influenced by other variables not examined in this study.